2021
DOI: 10.48144/prosiding.v1i.618
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Antioksidan Ekstrak Etanol Temu Blenyeh (Curcuma Purpurascens Blumae) Dengan Metode Dpph (1,1 Diphenyl-2-Picrylhydrazyl)

Abstract: Antioxidants have a function to scavenge and neutralize oxidation effect caused by free radicals by preventing the formation of radicals. Temu blenyeh (Curcuma purpurascens Bl) is one of the curcuma species which is still under-researched. Traditionally, temu blenyeh is used to treat stomachache, cough, itch, and skin infection. Some studies show that temu blenyeh extract had antioxidants activity and anti-cancer. The extract contains flavonoid, terpenoid, steroid, triterpenoid, essential oil. The study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Based on the DPPH test, Temu Blenyeh extract has high antioxidant activity with an antioxidant capacity equivalent to vitamin C (Jalip et al 2013;Pramiastuti et al 2021). Antioxidant test conducted by Jalip et al (2013) showed that the methanol extract of temu blenyeh rhizome had the highest antioxidant activity which was determined by measuring the total of flavonoid content (measured as quercetin) and free radical scav-enging activity of DPPH.…”
Section: Antioxidant Activity Of C Purpurascensmentioning
confidence: 99%
“…Based on the DPPH test, Temu Blenyeh extract has high antioxidant activity with an antioxidant capacity equivalent to vitamin C (Jalip et al 2013;Pramiastuti et al 2021). Antioxidant test conducted by Jalip et al (2013) showed that the methanol extract of temu blenyeh rhizome had the highest antioxidant activity which was determined by measuring the total of flavonoid content (measured as quercetin) and free radical scav-enging activity of DPPH.…”
Section: Antioxidant Activity Of C Purpurascensmentioning
confidence: 99%